(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
This article presents the geobotanical characteristics and ecological conditions of populations of the endemic species Galatella saxatilis found in the mountain gorge of Syugata. The natural conditions of the territory areconsidered: topography, soil cover, water resources, climate, where the object of research is found, and geobotanical characteristics of plant community types are compiled. The results are filled in the table and displayed in the figures. The percentage of yield of types in communities is calculated. The morphological features of the Galatella saxatilis species are described and the life States and quality level of generative stems are determined. During repeated observations of the species Galatella saxatilis, only 7 individuals were found in the first population. The second population contained 10 individuals. The following types are distinguished by life States: generative age(g1), mature(g2), old(g3) and postgenerative sub-senile(ss), senile(s). 24 plant species found in the population have been identified and a systematic list has been compiled. The main tasks of the research work were completed in full and successfully completed. Key words: topography, water resources, soil cover, climate, plant communities, forage yield, community types.